Zonated quantification of steatosis in an entire mouse liver. (1st June 2016) - Schwen, Lars Ole; Homeyer, André; Schwier, Michael; Dahmen, Uta; Dirsch, Olaf; Schenk, Arne; Kuepfer, Lars; Preusser, Tobias; Schenk, Andrea
Abstract: Many physiological processes and pathological conditions in livers are spatially heterogeneous, forming patterns at the lobular length scale or varying across the organ. Steatosis, a common liver disease characterized by lipids accumulating in hepatocytes, exhibits heterogeneity at both these spatial scales. The main goal of the present study was to provide a method for zonated quantification of the steatosis patterns found in an entire mouse liver. As an example application, the results were employed in a pharmacokinetics simulation. For the analysis, an automatic detection of the lipid vacuoles was used in multiple slides of histological serial sections covering an entire mouse liver. Lobuli were determined semi-automatically and zones were defined within the lobuli. Subsequently, the lipid content of each zone was computed. The steatosis patterns were found to be predominantly periportal, with a notable organ-scale heterogeneity. The analysis provides a quantitative description of the extent of steatosis in unprecedented detail. The resulting steatosis patterns were successfully used as a perturbation to the liver as part of an exemplary whole-body pharmacokinetics simulation for the antitussive drug dextromethorphan. The zonated quantification is also applicable to other pathological conditions that can be detected in histological images. Besides being a descriptive research tool, this quantification could perspectively complement diagnosis based on visual assessment of histological images. Abstract : Graphical abstract: Abstract : Highlights: A new spatial quantification shows heterogeneity of liver biomarkers on two scales. Steatosis was assessed in histological serial sections covering an entire mouse liver. The steatosis is distributed periportally with a notable variation across the organ. Steatosis distributions influence results of a whole-body pharmacokinetics simulation. This quantification can complement visual evaluation of histological images.